2017
DOI: 10.3390/molecules22101597
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic-Functionalized, Tannic Acid-Templated Mesoporous Silica as a New Support for Immobilization of NHase

Abstract: Tannic acid-templated mesoporous silica (TAMS) was synthesized using a simple nonsurfactant template method and dopamine-functionalized TAMS (Dop-TAMS), which was prepared via a biomimetic coating, was developed as a new support for immobilization of NHase (NHase@Dop-TAMS). The Dop-TAMS was thoroughly characterized by the transmission electron microscopy (TEM), scanning electron microscopy (SEM), Brunauer–Emmett–Teller (BET), and Fourier transform infrared (FT-IR) and the results showed that the Dop-TAMS posse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 47 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…19 20 One route to achieve higher retention of tannins in chemical formulations is to combine them with binding compounds 17,18 or nanoparticles to complexes 19 that can act as bridging or crosslinking agents between the matrix and tannin. Immobilization of tannin, or specific hydrolysable tannin compounds such as tannic acid, onto material surfaces has also been achieved using for instance mesoporous silicate 20 , silica microspheres 21 , collagen 22 , graphene 23 and activated carbon 24 . As reported by Xu et al (2017), dialdehyde nanocellulose can be used to covalently 26 immobilize tannin molecules.…”
Section: Introductionmentioning
confidence: 99%
“…19 20 One route to achieve higher retention of tannins in chemical formulations is to combine them with binding compounds 17,18 or nanoparticles to complexes 19 that can act as bridging or crosslinking agents between the matrix and tannin. Immobilization of tannin, or specific hydrolysable tannin compounds such as tannic acid, onto material surfaces has also been achieved using for instance mesoporous silicate 20 , silica microspheres 21 , collagen 22 , graphene 23 and activated carbon 24 . As reported by Xu et al (2017), dialdehyde nanocellulose can be used to covalently 26 immobilize tannin molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The BET specific surface area of AC was 1358.2 (m 2 /g), and the BJH adsorption cumulative pore volume and pore diameter were 0.556 (cm 3 /g) and 3.20 (nm), respectively. Compared with AC, MSNM had a larger pore size and pore volume, which could be conducive to the smooth entry of LA molecules into the internal channels of MSNM, and also could improve the adsorption rate of LA by MSNM 27 .
Figure 4N 2 adsorption-desorption isotherms of the MSNM and AC.
…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies have demonstrated that plant biosurfactants have great potential for removal of metals with saponin from three types of soils (i.e., loamy sand, loam, silty clay, pH 6.1–7.2, 1.6–10.3% organic matter) spiked with Cu, Cd, and Zn [ 20 ] and for removal of arsenic (As) with tannic acid (TA) from soils (silty loam in texture, pH 4.4–7.9, 5.9–18.1% organic matter) in areas formerly used for As mining and smelting in Zloty Stok (Poland) [ 21 ]. Although plant biosurfactants are used less commonly than rhamnolipids, and TA is used less commonly than saponin, TA offers a number of advantages, namely, its low cost and nontoxicity [ 22 ]. TA is a naturally occurring plant polyphenol that is a type of hydrolyzable tannin, composed of a glucose moiety with numerous esterified gallic acid units.…”
Section: Introductionmentioning
confidence: 99%